Does e-service for research and community service boost the performance of university lecturers? - Sari, Dwi Oktaria; Putra, Raniasa; Alamsyah, Alamsyah (Intelektual Pustaka Media Utama, 2024)
Indonesian universities are implementing various strategies to improve the quality and quantity of scientific publications. Sriwijaya University has restructured its research and community service grant services by implementing e-services through the new generation management information system of the institute of research and community service (SIM LPPM NG). Numerous studies have been performed to determine the factors that influence lecturer performance, particularly in scientific journals. The purpose of this research is to utilize a model to investigate the impact of system quality, information quality, and service quality on user satisfaction and performance. For partial least squares structural equation modelling (PLS-SEM), 280 respondents comprised the dataset. The results demonstrated that system quality, information quality, and service quality influence user satisfaction. Individual performance is influenced by the level of user satisfaction. According to the findings of this study, the DeLone and McLean information system success model can be used to evaluate obligatory e-services that are integrated.